Unique Spectral Overlap and Resonant Energy Transfer between Europium(II) and Ytterbium(III) Cations: No Quantum Cutting. Issue 35 (19th July 2017) - Zhou, Lei; Tanner, Peter A.; Zhou, Weijie; Ai, Yeye; Ning, Lixin; Wu, Mingmei M.; Liang, Hongbin
Abstract: Samples of the Ca3 Sc2 Si3 O12 (CSS) host singly doped with Eu 2+ or Yb 3+, doubly doped with Eu 2+ and Yb 3+, and triply doped with Ce 3+, Eu 2+ and Yb 3+ were synthesized by a sol–gel combustion process under reducing conditions. Unlike previous reports of Eu 2+ →Yb 3+ energy transfer in other systems, the energy transfer is resonant in the CSS host and the transfer efficiency reaches 100 % for lightly doped samples. The transfer mechanism is multipolar rather than electron transfer for the sample compositions employed herein. The emission intensity of Yb 3+ is further enhanced by co‐doping with Ce 3+ in addition to Eu 2+ . The quantum efficiencies of the doped materials range between 9 % and 93 %. Abstract : Harvesting solar energy : Eu 2+ or Yb 3+ singly, Eu 2+ and Yb 3+ doubly, and Ce 3+, Eu 2+, and Yb 3+ triply doped Ca3 Sc2 Si3 O12 (CSS) host lattices were synthesized by a sol–gel combustion process under reducing conditions. The triply doped system is used for harvesting solar energy and converting it to Yb 3+ near‐infrared emission (dd=dipole–dipole and dq=dipole–quadrupole interactions, ET=electron transfer).